2022
DOI: 10.36923/jicc.v22i3.77
|View full text |Cite
|
Sign up to set email alerts
|

Delivering A Good Speech by Identifying the Interpersonal Meaning Found in Joe Biden’s Victory Speech: A Case on Systemic Functional Linguistics

Abstract: This research aims to classify the interpersonal meaning in Joe Biden’s victory speech. It is an interesting phenomenon because by revealing the interpersonal meaning, people can be assisted to be successful in communication. The researchers used a qualitative research design to answer the research question and chose content analysis since the results of data analysis were in descriptive phenomena, such as words, clauses, and utterances. The research findings showed that mood elements: found 174 subjects and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This is in line with Moloeng (2007) who says that in qualitative research, the key instrument is the reviewer or the researcher himself. Thus, the researcher must be 'validated' (Herman et al, 2022;Resmi et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…This is in line with Moloeng (2007) who says that in qualitative research, the key instrument is the reviewer or the researcher himself. Thus, the researcher must be 'validated' (Herman et al, 2022;Resmi et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Halliday in Herman, et al [3] found that the development of language competence is the ability to master three basic language functions which he called "meta-functions" of which the "ideational function" expresses content helps determine the speaker's way of seeing things, "interpersonal function" establishes and maintains relationships, defines social groups, identifies and strengthens personal characteristics and the "textual function" helps create a link between the language itself and the characteristics of the situation in which it is used, helping the speaker (or writer) construct paragraphs of discourse appropriate to the situation and at the same time assume that any linguistic unit is the actualization of the above three functions [4].…”
Section: Theory Of Language Abilitymentioning
confidence: 99%
“…Language teaching, especially English in Indonesia, has many benefits related to scientific development, socio-political communication, economics and culture, and even everyday life (Herman et al, 2022). Multicultural education in English teaching can also be applied to respect each other between existing cultures.…”
Section: Introductionmentioning
confidence: 99%